Influence of forest vegetation restoration on carbon increment after mining - Zou, Hang; Song, Yali (Scientific reports, 2023)
We have clarified the study area has a history of 65 years and has been restored for 6 years. This study investigated the carbon storage characteristics of undisturbed natural forests and restored mining vegetation in Yunnan Province, China. The goal was to quantify carbon reserves and increments to inform ecological restoration strategies. Four vegetation components (tree, shrub, herb, litter) and five soil layers (0–10, 10–20, 20–30, 30–40, 40–60 cm) were analyzed. In natural forest, the tree layer stored 60% of carbon (273 Mg ha −1 ), overwhelmingly dominating vegetation carbon stocks. Shrub, herb, and litter layers each comprised < 1%. Surface soil layers (0–30 cm) stored 64% of soil carbon. In the restored mining area, the tree layer contributed 75% of vegetation carbon increment (16 Mg ha −1 ), though stocks were lower than natural forest. Soil layers showed the highest carbon increment (69%) despite lower biomass than natural conditions. Unexploited forests thus exhibit robust carbon storage, while restored mining areas have weaker carbon gains, indicating recovery potential. Strategic interventions targeting soil quality, stimulating vegetation growth, and increasing carbon sequestration could significantly augment reserves and ecological functionality. Prioritizing vegetation succession and soil revitalization are paramount to ensuring ecological integrity and sustainable development. Fostering a positive regional ecological feedback loop will be pivotal. This research quantifies carbon storage differences between undisturbed and restored mining areas, highlighting soil and vegetation as critical targets for optimizing carbon sequestration and ecosystem recovery in degraded environments.